Cover Image, Volume 39, Issue 12. Issue 12 (17th November 2018) - Proietti Onori, Martina; Koopal, Balwina; Everman, David B.; Worthington, Jessica D.; Jones, Julie R.; Ploeg, Melissa A.; Mientjes, Edwin; van Bon, Bregje W.; Kleefstra, Tjitske; Schulman, Howard; Kushner, Steven A.; Küry, Sébastien; et al.
Abstract : On the Front Cover : This cover image is based on the Research Article The intellectual disability‐associated CAMK2G p.Arg292Pro mutation acts as a pathogenic gain‐of‐function by Martina Proietti Onori et al., Pages 2008–2024. DOI:10.1002/humu.23647 .